2016
DOI: 10.1124/pr.115.010991
|View full text |Cite
|
Sign up to set email alerts
|

Proteinases, Their Extracellular Targets, and Inflammatory Signaling

Abstract: Given that over 2% of the human genome codes for proteolytic enzymes and their inhibitors, it is not surprising that proteinases serve many physiologic-pathophysiological roles. In this context, we provide an overview of proteolytic mechanisms regulating inflammation, with a focus on cell signaling stimulated by the generation of inflammatory peptides; activation of the proteinase-activated receptor (PAR) family of G protein-coupled receptors (GPCR), with a mechanism in common with adhesion-triggered GPCRs (AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
70
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 356 publications
(390 reference statements)
1
70
0
3
Order By: Relevance
“…Coagulation proteases signal through G-protein coupled protease activated receptors (PAR) in a cell-specific manner4,27. In podocytes, but not in glomerular endothelial or tubular cells, aPC’s cytoprotective effect requires PAR35,28. Congruently, aPC failed to promote nuclear translocation of sXBP1 in PAR3 knockdown podocytes establishing that PAR3 is required for aPC mediated UPR reprogramming in podocytes (Supplemental Figure 6A).…”
Section: Resultsmentioning
confidence: 98%
“…Coagulation proteases signal through G-protein coupled protease activated receptors (PAR) in a cell-specific manner4,27. In podocytes, but not in glomerular endothelial or tubular cells, aPC’s cytoprotective effect requires PAR35,28. Congruently, aPC failed to promote nuclear translocation of sXBP1 in PAR3 knockdown podocytes establishing that PAR3 is required for aPC mediated UPR reprogramming in podocytes (Supplemental Figure 6A).…”
Section: Resultsmentioning
confidence: 98%
“…Interestingly, it was recently shown that the biological activities of these proteinases can be mediated through specific proteinase-activated receptor (PAR) activation. PARs are members of the G-protein-coupled family, seven-transmembrane domain receptors, and their activation occurs through proteolytic cleavage of the N-terminal domain by proteinases, leading to the generation of a new N-terminal “tethered ligand,” which binds to the receptor itself resulting in its autoactivation [1, 2]. Until now, four members of the PAR family were discovered: PAR 1 , PAR 3 , and PAR 4 which are activated by thrombin and PAR 2 that can be activated by trypsin, neutrophil proteinase 3, tissue factor/factor VIIa/factor Xa, mast cell tryptase, membrane-tethered serine proteinase-1, or gingipains [3, 4].…”
Section: Introductionmentioning
confidence: 99%
“…Although the structures and mechanisms related to the activation of these receptors are similar, they can be expressed by different cells; hence, in each cell, their activation may lead to distinct roles in pathophysiological processes, such as growth, development, inflammation, tissue repair, and pain [2, 710]. PAR 1 is expressed by platelets, osteoblast endothelial cells, epithelial cells, fibroblasts, myocytes, neurons, and astrocytes, and it seems to play an important role in injured tissues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2-furoyl-LIGRLO-NH 2 (2fLIGRLO) and SLIGRL-NH 2 . [11][12][13] A recent paper suggests that thrombin could activate PAR2 in situations, where high levels of active thrombin can be generated, such as in a tumor microenvironment or in the setting of acute tissue trauma. 14) Also, inflammatory stimuli, such as interleukin-1α and tumor necrosis factor-α, 15) can induce expression of PAR2 in the endothelium, which can lead * To whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%